PENGGUNAAN PROCESSING DALAM KOMPUTER GRAFIK - Meiyanto Eko Sulistyo (Jurusan Teknik Informatika, 2013)
Computer graphics is the study of how to create images and animations (image sequences) involving computers, both hardware (hardware) and software (the software). In this paper, we will discuss the basics of using the Processing programming language computer graphics. The author conducted basic experiments using Processing on making size (size) in the window display, point (point), line (line), triangle (triangle), quadrilateral (quad), rectangular (rect), and ellipse (ellipse), as well as the shape coordinate system. Of the experiments that have been performed, resulting in a positive y coordinate position starting from zero which is located in the top left corner heading down, and look up the appropriate forms with the dharapkan.